Identificação de biomarcadores proteômicos salivares em idosos ativos e sedentários - Pacheco, Valéria Marques Bordallo (2020)
Proteomic analyzes in the elderly population have been used to find biomarkers that may be associated with many age-related diseases, such as Alzheimer's disease, diabetes, coronary heart disease and hypertension. However, the definition of biomarkers related to the effects of regular exercise on the health-disease process of the elderly is lacking in the literature. Thus, the aim of this study was to identify proteomic biomarkers in the salivary fluid of active and sedentary elderly people. Five physically active and five sedentary elderly people were recruited. Total unstimulated saliva was collected from all individuals for analysis of the salivary proteome that was performed by LC-MS / MS. For the evaluation of oral health, the DMFT index, visible supra gingival plaque, bleeding on probing and suppuration, in addition to the probing depth measurement (mm) were used. Prosthesis use and need and salivary flow (ml / min) were also evaluated. Functional capacity was assessed using the IGAF (physical tests), in addition to socio-demographic assessments and medical history. Proteomic and clinical results were computed to assess and correlate protein patterns in active and sedentary elderly.148 exclusive proteins were found in the active group, 154 exclusive in the sedentary group and 240 proteins common to the 2 groups. In the statistical analysis, 10 proteins stood out, 4 less expressed in the active group and more expressed in the sedentary group: Alpha-2-macroglobulin, Complement C3, Serotransferrin and Brain acid soluble protein 1. And the other 6 more expressed in the active group and less expressed in the sedentary group: Lactotransferrin, Alpha-amylase 1, S100-A8, S100-A9, Lactoperoxidase, and Galetin-3 binding protein. No difference was found in oral health between the groups of active and sedentary elderly, they are all independent in relation to activities of daily living. As for the IGAF, the mean in the active elderly was 71 and in the sedentary by 48.7 (variance of 73.75 and 136.45, respectively) and the p-value of 0.0088.The salivary proteome of active and sedentary elderly people showed differences in the presence of biomarkers for Alzeimer disease, thyroid and ovarian cancer and a potential biomarker for predicting breast cancer lymph node metastasis.This innovative study may result in the development of a better method of treating age-related diseases and in preventing or reducing the appearance of pathologies associated with the aging process.